Shape and spatial working memory capacities are mostly independent - Sanada, Motoyuki; Ikeda, Koki; Hasegawa, Toshikazu (Frontiers in Psychology, 2015)
Whether visual working memory consists of a common storage resource or of multiple subsystems has been a controversial issue. Logie (1995) suggested that it can be divided into visual (for color, shape, objects, etc.) and spatial working memory (for location). However, a recent study reported evidence against this hypothesis. Using a dual task paradigm, Wood (2011) showed interference between shape and spatial working memory capacities, suggesting that they share a common resource limitation. We re-examined this finding controlling possible confounding factors, including the way to present spatial location cues, task order, and type of working memory load to be manipulated. The same pattern of results was successfully reproduced, but only in a highly powered experiment (N = 90), and therefore the size of interference was estimated to be quite small (d = 0.24). Thus, these data offer a way to reconcile seemingly contradicting previous findings. On the one hand, some part of the storage system is genuinely shared by shape and spatial working memory systems, confirming the report of Wood (2011). On the other hand, the amount of the overlap is only minimal, and therefore the two systems should be regarded as mostly independent from each other, supporting the classical visuo-spatial separation hypothesis (203 words)